Computational thermochemistry of glycolaldehyde. Issue 8 (5th June 2012) - Bleda, Erdi A.; Yavuz, Ilhan; Altun, Zikri; Trindle, Carl
Abstract We use a variant of the focal point analysis to refine estimates of the relative energies of the four low‐energy torsional conformers of glycolaldehyde. The most stable form is the cis‐cis structure which enjoys a degree of H‐bonding from hydroxyl H to carbonyl O; here dihedral angles τ1 (OCCO) and τ2 (CCOH) both are zero. We optimized structures in both CCSD(T)/aug‐cc‐pVDZ and aug‐cc‐pVTZ; the structures agree within 0.01 Å for bond lengths and 1.0 degrees for valence angles, but the larger basis brings the rotational constants closer to experimental values. According to our extrapolation of CCSD(T) energies evaluated in basis sets ranging to aug‐cc‐pVQZ the trans‐trans form (180°, 180°) has a relative energy of 12.6 kJ/mol. The trans‐gauche conformer (160°, ±75°) is situated at 13.9 kJ/mol and the cis‐trans form (0°, 180°) at 18.9 kJ/mol. Values are corrected for zero point vibrational energy by MP2/aug‐cc‐pVTZ frequencies. Modeling the vibrational spectra is best accomplished by MP2/aug‐cc‐pVTZ with anharmonic corrections. We compute the Watsonian parameters that define the theoretical vibrational‐rotational spectra for the four stable conformers, to assist the search for these species in the interstellar medium. Six transition states are located by G4 and CBS‐QB3 methods as well as extrapolation using energies for structures optimized in CCSD(T)/aug‐cc‐pVDZ structures. We use two isodesmic reactions with two well‐established thermochemical computational schemes G4 and CBS‐QB3 to estimate energy enthalpy and Gibbs energy of formation as well as the entropy of the gas phase system. Our extrapolated electronic energies of species appearing in the isodesmic reactions produce independent values of thermodynamic quantities consistent with G4 and CBS‐QB3. © 2013 Wiley Periodicals, Inc.